Enzyme annotation for orphan reactions and its applications in biomanufacturing - Zhen Zhang; Chun Li (Green Chemical Engineering, 2023)
There are lots of biochemical reactions in the biosynthetic pathway without associated enzymes. Reactions predicted by retro-biosynthetic tools are not assigned gene sequences. Besides, non-natural reactions designed with novel functions also lack suitable enzymes. All these reactions can be categorized as orphan reactions. The absence of protein-encoding genes in these orphan reactions limits their direct experimental implementation. Computational tools have been developed to find candidate enzymes for these orphan reactions. Herein, we discuss recent advances in these computational tools, including reaction similarity-based methods for calculating the substructural similarity between orphan reactions and known enzymatic reactions; sequence-based tools combine metabolic knowledge base and phenotypic information with genomic, transcriptomic, and metabolomic data to mine appropriate enzymes for orphan reactions; and approaches based on the creation of enzyme variants for orphan reactions as enzyme engineering modifications and de novo design of enzymes. We believe that our review will greatly facilitate the design of microbial cell factories and contribute to the development of the biomanufacturing field.